PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 5 SUNGAI SELARI KECAMATAN BUKIT BATU - Ruslina Ruslina; lazim.N lazim.N; Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the poor results of students' mathematics learning with an average value of 61.6 preliminary data. Formulation of the problem in this research is the study of mathematics Is realistic approach application (PMR) can improve learning outcomes fourth grade math student Negeri 5 Selari River Bukit Batu subdistrict? The purpose of this research is to improve learning outcomes fourth grade math student Negeri 5 Sungai Bukit Batu subdistrict Selari with the application of Realistic Mathematics Education approach (PMR. The design of this study classroom action research (PTK) which performed a total of two cycles, each cycle consisting of twice meeting and one harian.dari replications of this research study The results obtained scores of students on the basis of the average value of 62 increased by 71 in the first cycle and the second cycle values increased an average score of 77. The completeness classical on the basis of 40% (10 students) who did not complete 60% (15 students). In the first cycle increased mastery repetition to 68% (17 students) who did not complete 32% (8 students). In classical completeness repeat second cycle increased to 92% (23 students), which is not complete 8% (2 students). The results of the data analysis activities of teachers and students from the first cycle of teacher activity, the first meeting both categories with a percentage of 70%. At the second meeting with both categories the percentage increases to 75%. In the second cycle category first meeting very well with the percentage of 85%, and at the meeting of two categories was also very good with a percentage of 90%. The observation of student activity first cycle, the first meeting with the category enough percentage of 60%, in the second meeting of both categories with a percentage of 65%. In the second cycle the first meeting both categories with a percentage of 75%, and the fifth meeting of the very good category with a percentage of 90%. From the above explanation, the researchers conducted a study entitled "Application of Realistic Mathematics Learning Approach (PMR) to Improve Learning Outcomes Mathematics Elementary School fourth grade students 5 Selari River Bukit Batu subdistrict.Keywords: Realistic Mathematics Education (PMR), the result of learning Mathematics